The Proteasomal Substrate Stm1 Participates in Apoptosis-like Cell Death in Yeast - Ligr, Martin (The American Society for Cell Biology, 2001)
We have identified the yeast gene STM1 in an overexpression screen for new proteasomal substrates. Stm1 is unstable in wild-type cells and stabilized in cells with defective proteasomal activity and thus a bona fide substrate of the proteasome. It is localized in the perinuclear region and is required for growth in the presence of mutagens. Overexpression in cells with impaired proteasomal degradation leads to cell death accompanied with cytological markers of apoptosis: loss of plasma membrane asymmetry, chromatin condensation, and DNA cleavage. Cells lacking Stm1 display deficiency in the apoptosis-like cell death process induced by treatment with low concentrations of H(2)O(2). We suggest that Stm1 is involved in the control of the apoptosis-like cell death in yeast. Survival is increased when Stm1 is completely missing from the cells or when inhibition of Stm1 synthesis permits proteasomal degradation to decrease its amount in the cell. Conversely, Stm1 accumulation induces cell death. In addition we identified five other genes whose overexpression in proteasomal mutants caused similar apoptotic phenotypes.